2009
DOI: 10.1002/jssc.200900358
|View full text |Cite
|
Sign up to set email alerts
|

Matrix effects observed during pesticides residue analysis in fruits by GC

Abstract: The influence of the sample matrix in the GC-electron-capture detection analysis of the pesticides dimethoate, diazinon, chlorothalonil, parathion methyl and fenitrothion in fruits samples has been studied. Experiments have been carried out where the pesticide responses in standard solutions prepared in selected solvent were compared with their response when present in apple, mango, papaya, banana, pineapple and melon extracts. The presence of matrix effects (MEs) and their extent were shown to be simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Since the matrix effect changes from one sample to another, i.e. depends on the matrix type, some authors have suggested the application of the matrixmatched calibration method [11], which is considered as one of the most practical solutions. When no blank matrix is available for the matrix-matched calibration procedure, a standard-addition method is performed [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the matrix effect changes from one sample to another, i.e. depends on the matrix type, some authors have suggested the application of the matrixmatched calibration method [11], which is considered as one of the most practical solutions. When no blank matrix is available for the matrix-matched calibration procedure, a standard-addition method is performed [17].…”
Section: Resultsmentioning
confidence: 99%
“…Matrix effect -dilution trendline is similar for all pesticides. Another study, dealing with the response of several pesticides in the apple matrix, demonstrated the dependence of the matrix effect on the matrix concentration -a gradual increase in response of dimethoate, chlorothalonil and fenitrothion was observed, as the matrix concentration in the solutions increased from 0.1 to 1.0 g mL -1 [11]. The study furthermore revealed that besides matrix concentration, the matrix effect depends on the matrix type, pesticide concentration and analytical range.…”
Section: Gc-ms Analysismentioning
confidence: 90%
“…One of the most used methods to compensate them is the development of a matrix matched calibration (De Sousa Freitas & Lanças, 2009;Zrostlíková, Hajšlová, Poustka, & Begany, 2002), which was also carried out in this work. For this purpose, comparison of the slopes and intercepts of the calibration curves of pure standards dissolved in cyclohexane and of pure standards dissolved in the final sample extract (which is also cyclohexane) was developed.…”
Section: Matrix Matched Calibration and Matrix Effect Evaluationmentioning
confidence: 99%
“…In addition, it has been briefly noted in EU analytical guideline SANTE/11945/2015 that the detector response of individual pesticides in multipesticide calibration standards may be affected by one or more of the other pesticides in the same solution (http://ec.europa.eu/food/plant/docs/plant_pest-icides_mrl_guidelines_wrkdoc_11945_en.pdf"). However, this unnamed phenomenon has been rarely studied compared to the "matrix effect" in GC analysis, which has been studied widely [1][2][3][4]6,13,15,19,21,[25][26][27]. To the best of our knowledge, the response-altering phenomenon resulting from several coexisting pesticides has not been demonstrated in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%